THE LIFE QUALITY OF BUYNAKSK CITY INHABITANTS, REPUBLIC OF DAGESTAN (POPULATION STUDY) - G. M. Abdurakhmanov; P. I. Gabibova; P. A. Bekshokova (Юг России: экология, развитие)
Aim. We studied the life quality indicators of the population in Buynaksk city, Dagestan, in a random representative sample of 315 people (155 women and 160 men) aged between 18 and 76 years. Respondents were divided into 3 age groups (up to 35 years, 35-50 years and 50 years and older).Methods. The study was performed using a common health survey – Medical Outcomes Study-Short Form-36 (SF-36) in accordance with the requirements of the International Quality of Life Assessment Project (IQOLA).Results. We conducted a comparative analysis of age dynamics of population quality of life, as well as the male and female population of the study sample. The highest quality of life indicators are found on the scales of social (SF) and physical functioning (PF) – 83.4 and 82.9 points, respectively, the lowest – on the scale of general health (GH)– 58.6. In general, with aging, there is a decrease of life quality among both male and female population. The most marked age-related changes are observed on the scale of role-physical functioning (RF) and physical functioning (PF) – 54.2 and 48.0% respectively and the least marked on the scale of mental health – 4.4%. The value of the integral index of quality of life in population-based study in Buynaksk city, Republic of Dagestan was 583.4.Conclusion. The research findings might be used in planning, developing and evaluating the effectiveness of various reforms, health and socio-economic programs being implemented in the region as well as to improve the quality of life and well-being.